Effects of yoga-based interventions on cognitive function in healthy older adults: A systematic review of randomized controlled trials. (May 2021) - Hoy, Sara; Östh, Josefine; Pascoe, Michaela; Kandola, Aaron; Hallgren, Mats
Highlights: The current systematic review included 6 RCTs (5 unique trials), evaluating effects of yoga on cognitive function in healthy older adults. Four out of six studies reported significant positive effects on cognition, including gross memory functioning and executive functions. The yoga-based intervention characteristics and assessment methods varied between studies. Future studies should explicitly report the intervention characteristics associated with changes in cognitive function. Adequately powered RCTs with robust study designs and long-term follow-ups are required. Abstract: Background: The world's elderly population is growing. Physical activity has positive effects on health and cognition, but is decreasing among the elderly. Interest in yoga-based exercises has increased in this population, especially as an intervention targeting balance, flexibility, strength, and well-being. Recent interest has arisen regarding yoga's potential benefits for cognition. Objective: To systematically review evidence from randomized controlled trials (RCTs) examining the effects of yoga-based interventions on cognitive functioning in healthy adults aged ≥60. A secondary aim was to describe intervention characteristics and, where possible, the extent to which these influenced study outcomes. Method: The review was conducted in accordance with PRISMA guidelines. Searches were performed from inception to June 2020 using the following electronic databases: (1) PubMed (NLM); (2) Embase (Elsevier); (3) Cochrane Central (Wiley); (4) PsycINFO (EBSCOhost); and (5) Cinahl (EbscoHost). Inclusion criteria: RCTs of yoga-based interventions assessing cognition in healthy adults ≥60 years. Risk of bias was assessed using the revised Cochrane risk of bias tool. Results: A total of 1466 records were initially identified; six studies (5 unique trials) were included in the review. Four of the six articles reported significant positive effects of yoga-based interventions on cognition, including gross memory functioning and executive functions. Intervention characteristics and assessment methods varied between studies, with a high overall risk of bias in all studies. Conclusion: Yoga-based interventions are associated with improvements in cognition in healthy older adults. Adequately powered RCTs with robust study designs and long-term follow-ups are required. Future studies should explicitly report the intervention characteristics associated with changes in cognitive function.